Study the toxic effect of the herbicide Gold topik (80EC) on survival and behavior of mosquito fish (Gambusiaholbrooki Girard 1859) - Teeba Najim Hassan; Maha Abdulnabi Gathwan (Journal of Madenat Alelem University College, 2017)
The experiment was carried out to study the toxic effect of the herbicide Gold Topik (80EC) on survival and behavior of mosquito fish Gambusia holbrooki . The mean lethal concentration (LC50) and differences between concentrations were determined during 24 hrs exposure and been measured using ANOVA methods at significant level (P<0.005). Ascending concentrations of Gold Topik (80EC) (7.7 ,8.7 ,9.7 ,10.7 ,11.7 ,12.7 ,13.7 ,14.7 mg/l) were used to determine. The value of LC50 was 11.7 mg/l. The mortality rate was increased with increasing the concentrations. Results of present study showed some abnormal behaviors including erratic and irregular swimming , decrease the feeding intensity , in addition to loss balance and increase the movements of operculum ,these symptoms lead to death of fish.